EXPERIENTIAL VALUE AS A DRIVER OF BRAND LOVE AND CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION IN THE SLOW BAR COFFEE SHOP TOKO KOPI LAJENG - Rama; Putu Nina Madiawati; Arry Widodo (PT. Jurnal Center Indonesia Publisher, 2026)
The increasing popularity of slow bar coffee shops in Indonesia reflects a shift in consumer preferences towards more personalized, immersive, and educational coffee experiences. This study aims to examine the effect of Experience Value, consisting of Customer Return on Investment (CROI), Service Excellence, Aesthetics, and Enjoyment, on Brand Love and Customer Loyalty through the mediating role of Customer Satisfaction among customers of Lajeng Coffee Shop in Bandung. A quantitative survey was conducted using purposive sampling, collecting 251 valid responses through a Likert scale questionnaire, and the data were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS. The results show that Experience Value has a significant effect on Customer Satisfaction (β = 0.721; p < 0.001). Customer Satisfaction acts as a partial mediator in the relationship between Experience Value and Brand Love and Customer Loyalty. Furthermore, the effect of Customer Satisfaction on Customer Loyalty (β = 0.462; p < 0.001) is stronger than its effect on Brand Love (β = 0.441; p < 0.001), indicating that satisfaction is more easily translated into loyal behavior than into emotional attachment. These findings extend customer experience research in the slow bar context and offer practical guidance for managers to prioritize experience investments that strengthen loyalty and brand love.